Pengaruh Online Customer Review Dan Online Customer Rating Terhadap Keputusan Pembelian Konsumen Pada E-Commerce Carousell (Studi Kasus Pada Pengguna Carousell Kecamatan Medan Selayang) - Sinaga, Nico Daniel; Siregar , Dahrul (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study is to analyze the influence of online customer reviews and online customer ratings on consumer purchasing decisions among Carousell application users in Medan Selayang District. This research employs an associative quantitative approach with a total of 96 respondents selected using a non-probability sampling technique with a purposive sampling method. Data were collected through online questionnaires and analyzed using multiple linear regression. The results indicate that online customer reviews (β = 0.437; p = 0.000) and online customer ratings (β = 0.322; p = 0.014) have a positive and significant effect on purchasing decisions. Simultaneously, both variables also show a significant effect on purchasing decisions (F = 61.357; p = 0.000) with an R² value of 0.560. These findings highlight that consumer reviews and star ratings on the Carousell platform play an important role in influencing users’ purchasing decisions.